Pengembangan Ekonomi Desa Maritim Melalui Pelatihan Produksi “Eungkot Keumamah” Kepada Kelompok Perempuan di Gampong Pusong Lama Kota Lhokseumawe - Mujiburrahman; Ade Ikhsan Kamil; Aflia Riski; Ibrahim Chalid; Meliza, Richa; Suadi Zainal (Universitas Malikussaleh, 2026)
Pusong Lama Village is a fishing village with extraordinary marine natural potential. In addition to being directly adjacent to the sea, the village also has a Fish Landing Port (PPI) located within the village area. Due to this strategic location, the village has easy access to fish, especially skipjack tuna. As a maritime village, the people of Pusong Lama face social problems commonly experienced by fishing communities, namely economic vulnerability. In fact, the village has great potential for the development of a creative economy. One such potential is the abundant availability of skipjack tuna. However, so far this potential has not been optimally utilized to encourage the household economy of fishermen as a source of family income. During certain seasons, the abundance of skipjack tuna forces it to be sold at very low prices and even discarded as fish waste, which is only used as feed for catfish. Based on the existing potential and problems in the target village, the proposed solution is to improve community skills in utilizing fisheries potential through training in producing keumamah. The purpose of improving these skills is that the ability to produce keumamah can help support the economic resilience of fishermen’s families. The expected outcome of this training is that the community, through women’s groups, will gain the skills and capacity to produce keumamah as an economically valuable commodity. To achieve this objective, women’s groups are formed as the main target, and intensive training and mentoring are carried out using a tiered, gradual, and sustainable approach.